Enhancing crop yields through improvements in the efficiency of photosynthesis and respiration. Issue 1 (17th November 2022) - Garcia, Andres; Gaju, Oorbessy; Bowerman, Andrew F.; Buck, Sally A.; Evans, John R.; Furbank, Robert T.; Gilliham, Matthew; Millar, A. Harvey; Pogson, Barry J.; Reynolds, Matthew P.; Ruan, Yong‐Ling; Taylor, Nicolas L.; et al.
Summary: The rate with which crop yields per hectare increase each year is plateauing at the same time that human population growth and other factors increase food demand. Increasing yield potential ( Y p ) of crops is vital to address these challenges. In this review, we explore a component of Y p that has yet to be optimised – that being improvements in the efficiency with which light energy is converted into biomass ( ε c ) via modifications to CO2 fixed per unit quantum of light ( α ), efficiency of respiratory ATP production ( ε prod ) and efficiency of ATP use ( ε use ). For α, targets include changes in photoprotective machinery, ribulose bisphosphate carboxylase/oxygenase kinetics and photorespiratory pathways. There is also potential for ε prod to be increased via targeted changes to the expression of the alternative oxidase and mitochondrial uncoupling pathways. Similarly, there are possibilities to improve ε use via changes to the ATP costs of phloem loading, nutrient uptake, futile cycles and/or protein/membrane turnover. Recently developed high‐throughput measurements of respiration can serve as a proxy for the cumulative energy cost of these processes. There are thus exciting opportunities to use our growing knowledge of factors influencing the efficiency of photosynthesis and respiration to create a step‐change in yield potential of globally important crops.